2020
DOI: 10.1137/19m1244494
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Characterization of Complex-Balanced, Detailed-Balanced, and Weakly Reversible Systems

Abstract: Very often, models in biology, chemistry, physics and engineering are systems of polynomial or power-law ordinary differential equations, arising from a reaction network. Such dynamical systems can be generated by many different reaction networks. On the other hand, networks with special properties (such as reversibility or weak reversibility) are known or conjectured to give rise to dynamical systems that have special properties: existence of positive steady states, persistence, permanence, and (for well-chos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Another method, staying within the realm of mass-action systems, is that of dynamical equivalence. The associated dynamical system (1) of a mass-action system G κ is uniquely defined; however, different reaction networks can give rise to the same system of differential equations under mass-action kinetics [14,34,11]. We say that a system of differential equationsẋ = f (x) can be realized by a network G if there exists a vector of rate constants κ > 0 such that the associated dynamical system of G κ isẋ = f (x).…”
Section: Dynamical Equivalencementioning
confidence: 99%
See 2 more Smart Citations
“…Another method, staying within the realm of mass-action systems, is that of dynamical equivalence. The associated dynamical system (1) of a mass-action system G κ is uniquely defined; however, different reaction networks can give rise to the same system of differential equations under mass-action kinetics [14,34,11]. We say that a system of differential equationsẋ = f (x) can be realized by a network G if there exists a vector of rate constants κ > 0 such that the associated dynamical system of G κ isẋ = f (x).…”
Section: Dynamical Equivalencementioning
confidence: 99%
“…Indeed, two massaction systems are dynamically equivalent if and only if the corresponding fluxes at an arbitrary state satisfy (6) for every vertex. See [11] for the correspondence between mass-action systems and fluxes on a network.…”
Section: Dynamical Equivalencementioning
confidence: 99%
See 1 more Smart Citation
“…In various important cases, it has been shown that positive CB equilibria are globally stable (Anderson 2011;Craciun et al 2013), a property that is conjectured to hold for all CB systems (Horn 1974;Craciun 2015). Finally, mass-action systems that are not CB may be dynamically equivalent to CB systems and have all their strong properties (Craciun et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, mass-action systems that are not CB may be dynamically equivalent to CB systems and have all their strong properties (Craciun et al. 2020 ).…”
Section: Introductionmentioning
confidence: 99%